Relationship between demographic and cephalometric measures and electromyographic activityu of the facial musculature. A preliminary study in children and adolescents - Jiménez-García, Alejandra Ester; Rosell Clari, Vicent; Paredes-Gallargo, Vanessa (Revista de Investigación en Logopedia, 2022)
Surface electromyography (EMGS) is used to evaluate the electromyographic activity of the orofacial musculature at rest, or when performing certain activities such as swallowing saliva or water, or tasks of maximum voluntary contraction. Numerous studies have evaluated the relationship between facial morphology and muscle activity, with contradictory results. The aim of this study was to determine whether there are significant differences in the electromyographic activity of the orofacial musculature as a function of the variables: age, height, weight, facial pattern and skeletal class. For this purpose, 81 patients with dental malocclusion were selected (35 males and 46 females, aged 6 to 17 years). Bilateral EMGS activity of the temporalis, masseter, orbicularis oris of the upper and lower lip of the mouth and suprahyoid muscles was measured in the resting position, maximum voluntary contraction and swallowing of saliva 2 ml of water. The results obtained show that the mandibular plane and the ANB angle present significant differences in all the variables of EMGS activity; however, the facial pattern only shows significant differences in the mean deviation of muscle activity. Skeletal class shows no significant effect on any of the EMGS variables recorded. The variables Age, Weight and Height show significant results on all EMGS activity variables. The variable Sex only shows significant results in the mean deviation of muscle activity. This work supports previous studies that found no significant results based on facial pattern and skeletal class. It would be advisable to perform a more exhaustive analysis of the muscles involved and their relationship between the different tasks evaluated, and to increase the sample size of patients with skeletal Class III in order to reach more definitive conclusions.
Keywords: demographic variables; facial pattern; masticatory muscles activity; surface electromyography; skeletal class